How increased volume of low-stakes testing improved student engagement and performance without additional grading burden - Saccucci, Frank (My University, 2023)
In his chapter, Franco (Frank) Saccucci contributes to this book, Enhancing Student Learning Outcomes in Higher Education, by illustrating how an increased volume of low-stakes testing in the classroom improved student engagement and performance without causing additional educator fatigue to either the marking efforts or budget. He relates to the three phases of the central ESLO model of the book in this way: In the DESIGNING phase, he explains why and how he developed the approach incorporating regular low-stakes testing into his teaching approach. He demonstrates how quizzes are carefully planned to strengthen students’ memory and practical use of formulas, while a peermarking system is introduced to reduce the teacher fatigue from grading. In the DOING phase, he describes how he implements low-stakes testing in the classroom setting. Short quizzes are seamlessly integrated into class sessions, and the peer-marking system actively engages students in a less conventional aspect of the learning process. The approach fosters a ‘gamified’ atmosphere that further motivates student engagement and participation while ensuring consistent oversight of the effectiveness of the process across different institutions. In the DIAGNOSING phase, the author evaluated the effectiveness of this teaching approach through student surveys and direct observations of student performance. The survey feedback indicated an increased preference for this testing method and improved readiness for major exams. The observations supported enhanced student engagement, demonstrating the success of the intervention in improving learning and performance. An unexpected outcome was the gamification of the learning process, which further enhanced student motivation.
Keywords: low-stakes testing; student engagement; higher education